Covid-19 and the danger of self-sufficiency: How Europe's pandemic resilience was helped by an open economy - Johan Norberg (European Centre for International Political Economy (ECIPE), 2021)
During the Covid-19 pandemic, Europe has benefitted strongly from being an open economy that can access goods and services from other parts of the world. Paradoxically, some politicians in Europe think that dependence on foreign supplies reduced the resilience of our economy - and argue that Europe now should wean itself off its dependence on other economies. In this Policy Brief, it is argued that self-sufficiency or less economic openness is a dangerous direction of policy. It would make Europe less resilient and less capable of responding to the next emergency. It is key that people, firms and governments can get supplies from other parts of the world. It is diversification, not concentration of production, that will make Europe more resilient when the next emergency hit. We don't know where the next crisis will come from. Nature will throw nasty surprises at us, and we will make stupid mistakes, some of which will have devastating consequences. What we do know, though, is that we stand a better chance to fight the next emergency if we get richer and improve our technology. The best policy for resilience is one that encourages specialisation and innovation - and, when the emergency hit, allow for people to improvise in search for solutions. For that to happen, we need openness to goods, services and technology from abroad.
Keywords: 330; Protektionismus; Coronavirus; Offene Volkswirtschaft; Epidemie; EU-Staaten; Globalisierung